Avaliação dos efeitos de concentrações subletais de dimetoato no cérebro e ventrículo de Apis mellifera africanizada - Barbosa, Rodrigo Avelaira [UNESP] (2015)
Africanized honey bees have great economic importance for Brazilian agriculture once they pollinate several crops. Agriculture has become quite dependent on the intensive use of pesticides, especially insecticides, endangering beneficial insects as these bees. Dimethoate is an insecticide widely used in the country and is applied in several crops pollinated by these insects. Its action takes place in the brain of these animals, inducing the inhibition of the enzyme acetylcholinesterase (AChE), which results in paralysis followed by death. It also has systemic action in plants, so that residues in nectar collected can reach the colony and be introduced to the feeding of the individuals who compose it. The midgut of bees makes the digestion and absorption of ingested substances, as well as producing detoxifying enzymes such as carboxylesterase (CaE). The objectives of this work were to evaluate the oral toxicity of dimethoate to Africanized honey bees and analyze the sublethal effects of this insecticide on survival, on the enzymatic activity of AChE and CaE, and on the histological, histochemical and ultrastructural characteristics of mushroom bodies and midgut of these bees. An oral toxicity test was conducted to determine the median lethal concentration (LC50) after 24 hours. Based on LC50 two sublethal concentrations were established (LC50/100 and LC50/10) to be tested on the survival assay and to be administered continuously on intoxication assays for 1, 5 and 13 days. The LC50 obtained was equivalent to 7.96 ± 0.45 ng a. i./μL diet, indicating high toxicity. Bees treated with LC50/100 had survival similar to the control group. Exposure to LC50/10 reduced survival. The LC50/100 promoted mild histological and histochemical changes in a few Kenyon cells from mushroom bodies. After 5 days, the LC50/10 promoted the AChE inhibition and the appearance of many condensed Kenyon cells with degraded organelles and irregular nucleus containing...